Ethylene Suppresses Abscisic Acid, Modulates Antioxidant System to Counteract Arsenic-Inhibited Photosynthetic Performance in the Presence of Selenium in Mustard - Sehar, Zebus; Iqbal, Noushina; Fatma, Mehar; Rather, Bilal A.; Albaqami, Mohammed; Khan, Nafees A. (Frontiers in Plant Science, 2022)
Arsenic (As) stress provokes various toxic effects in plants that disturbs its photosynthetic potential and hampers growth. Ethylene and selenium (Se) have shown regulatory interaction in plants for metals tolerance; however, their synergism in As tolerance through modification of the antioxidant enzymes, hormone biosynthesis needs further elaboration. With this in view, we investigated the impact of ethylene and Se in the protection of photosynthetic performance against As stress in mustard (Brassica juncea L.). Supplementation with ethephon (2-chloroethylphosphonic acid; ethylene source) and/or Se allayed the negative impact of As-induced toxicity by limiting As content in leaves, enhancing the antioxidant defense system, and decreasing the accumulation of abscisic acid (ABA). Ethylene plus Se more prominently regulated stomatal behavior, improved photosynthetic capacity, and mitigated As-induced effects. Ethephon in the presence of Se decreased stress ethylene formation and ABA accumulation under As stress, resulting in improved photosynthesis and growth through enhanced reduced glutathione (GSH) synthesis, reduced oxidative stress. In both As-stressed and non-stressed plants treated with ethylene action inhibitor, norbornadiene resulted in increased ABA and oxidative stress with reduced photosynthetic activity by downregulating expression of ascorbate peroxidase and glutathione reductase, suggesting involvement of ethylene in the reversal of As-induced toxicity. These findings suggest that ethephon and Se induce regulatory interaction between ethylene, ABA accumulation, and GSH metabolism through regulating the activity and expression of antioxidant enzymes. Thus, in an economically important crop (mustard) the severity of As stress could be reduced through the supplementation of both ethylene and Se that coordinate for maximum stress alleviation.